PHARMACOKINETICS AND BIODISTRIBUTION STUDIES OF DOXORUBICIN LOADED POLY(BUTYL CYANOACRYLATE) NANOPARTICLES SYNTHESIZED BY TWO DIFFERENT TECHNIQUES - Reddy, L. Harivardhan; Murthy, R. S. R. (Biomedical papers, 2004)
The aim of the study is to determine and compare the pharmacokinetics and tissue distribution of Doxorubicin (Dox) delivered as solution or through nanoparticles after intravenous (i.v.) and intraperitoneal (i.p.) injection. Doxorubicin loaded poly(butyl cyanoacrylate) nanoparticles were synthesized by dispersion polymerization (DP) and emulsion polymerization (EP) techniques. The drug loaded DP and EP nanoparticles were administered by i.v. or i.p. routes and the respective pharmacokinetics and tissue distribution were determined. Both types of nanoparticles significantly enhanced the elimination half-life (T1/2), mean residence time (MRT) AUC0-8, AUC0-∞ and AUMC0-8 of Dox in blood after i.v. injection. Dox delivered through DP nanoparticles rapidly disappeared from blood and distributed to the organs of reticuloendothelial system (RES). But, the clearance of Dox delivered through EP nanoparticles from blood was slower than this of the DP nanoparticles and Dox solution. After i.p. injection, the Dox loaded into DP nanoparticles quickly appeared in blood and undergone rapid distribution to the organs of RES, while the Dox loaded into EP nanoparticles absorbed slowly into blood and remained in the circulation for longer time. The absorption into blood of Dox delivered through DP and EP nanoparticles after i.p. injection was relatively rapid and higher than Dox solution. The T1/2, MRT, AUC0-8, AUC0-∞ and AUMC0-8 of Dox in blood were significantly higher and the clearance (Cl) was lower than for the Dox solution after i.p. injection. The tissue concentrations of Dox delivered through nanoparticles after i.p. injection were significantly lower than after i.v. injection. The bioavailability (F) of Dox was greatly enhanced by DP (∼1.9 fold) and EP nanoparticles (∼2.12 fold) compared to Dox solution after i.p. injection. EP nanoparticles significantly enhanced the bioavailability, MRT, T1/2, AUC0-8, AUC0-∞ and AUMC0-8 of Dox than DP nanoparticles. This signifies the advantage of EP nanoparticles in increasing the elimination half-life of Dox both after i.v. and i.p. injection and enhanced bioavailability after i.p. injection, which is expected to improve the therapeutic efficacy of Dox and reduce the Dox-associated systemic toxicity. Importantly, both DP and EP nanoparticles greatly reduced the distribution of Dox to heart both after i.v. and i.p. injection, suggesting their potential in reducing Dox-associated cardiotoxicity.
Keywords: Poly(butyl cyanoacrylate)/Nanoparticle/Emulsion polymerization/Long circulating carrier/Pharmaco kinetics/